2022
DOI: 10.3389/fcimb.2022.805170
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis to Identify Multi-Omic Correlations in the Lower Airways of Children With Cystic Fibrosis

Abstract: The leading cause of morbidity and mortality in cystic fibrosis (CF) is progressive lung disease secondary to chronic airway infection and inflammation; however, what drives CF airway infection and inflammation is not well understood. By providing a physiological snapshot of the airway, metabolomics can provide insight into these processes. Linking metabolomic data with microbiome data and phenotypic measures can reveal complex relationships between metabolites, lower airway bacterial communities, and disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…These results are consistent with previous studies that also found decreased levels of acylcarnitines in CF [58][59][60]. O'Connor et al, reported decreased levels of acylcarnitines that correlated with inflammation and the amount of bacteria in patients with CF, as a major finding of their recent untargeted metabolomic study in BALF samples [58]. Acylcarnitines are important for cellular energy production, mainly for the β-oxidation of fatty acids, as they are used as intermediates to transport acyl groups into the mitochondria [61].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with previous studies that also found decreased levels of acylcarnitines in CF [58][59][60]. O'Connor et al, reported decreased levels of acylcarnitines that correlated with inflammation and the amount of bacteria in patients with CF, as a major finding of their recent untargeted metabolomic study in BALF samples [58]. Acylcarnitines are important for cellular energy production, mainly for the β-oxidation of fatty acids, as they are used as intermediates to transport acyl groups into the mitochondria [61].…”
Section: Discussionsupporting
confidence: 94%
“…Figure 3 A–D shows box plots of carnitine, acetylcarnitine, propionylcarnitine and butyrylcarnitine. These results are consistent with previous studies that also found decreased levels of acylcarnitines in CF [ 58 , 59 , 60 ]. O’Connor et al, reported decreased levels of acylcarnitines that correlated with inflammation and the amount of bacteria in patients with CF, as a major finding of their recent untargeted metabolomic study in BALF samples [ 58 ].…”
Section: Discussionsupporting
confidence: 94%
“…The uid also contains endogenous peptides generated as products of protease activity on larger proteins, some of which have biological activity and can serve as biomarkers (11,12). Small molecule metabolites, acted upon by enzymes, are also detectable (13)(14)(15). Finally, extracellular vesicles, packed with nucleic acids, proteins and other molecule types have also been well-described (16,17).…”
Section: Introduction Balf: a Valuable Clinical Sample For Studying L...mentioning
confidence: 99%
“…Prevotella spp. is one of the dominant commensals that inhabits in multiple body locations of human and animal, such as gut [18], airways [19], and oral cavity [20]. Increasing studies revealed that dysbiosis of Prevotella genus is related to various diseases, including cystic brosis [19], gout [21], and obesity [22], although direct causation of disease remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…is one of the dominant commensals that inhabits in multiple body locations of human and animal, such as gut [18], airways [19], and oral cavity [20]. Increasing studies revealed that dysbiosis of Prevotella genus is related to various diseases, including cystic brosis [19], gout [21], and obesity [22], although direct causation of disease remains uncertain. In the present study, we found that Prevotella genus in gut microbiota was enriched in breast cancer patients, which is accordant with the report by Zhu and colleagues [8].…”
Section: Introductionmentioning
confidence: 99%